Digital Economy: New Opportunity in Technological Era - Aminah, Siti; Navandi, Dhony (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The Digital Economy has become one of the maining driving forces in global economic development. Bringing new opportunities that were previously unreachable by the traditional sector. This study aims to analyze the opportunities and challenges that arise in the digital economy in the technological era. Through a qualitative descriptive approach, this study indentifies the development of the digital economy, covering key sectors such as e-commerce fintech, and industry, and it’s impact on the global economy. Key findings show that the digital economy offers great potential for growth and efficiency, and expanding market access and financial inclusion. However, challenges such as infrastructure gaps data security, and digital literacy need to be addressed to maximize this potential. Collaboration between government, the private sector, and society is essential to create polices that support innovation and protect privacy and personal data. With the right approach, the digital economy can contribute to more inclusive and sustainable economic development.